2020
DOI: 10.1101/2020.10.26.356386
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pausing after clap reduces power required to fling wings apart at low Reynolds number

Abstract: The smallest flying insects such as thrips (body length < 2 mm) are challenged with needing to move in air at chord-based Reynolds number (Rec) on the order of 10. Pronounced viscous dissipation at such low Rec requires considerable energetic expenditure for tiny insects to stay aloft. Free-flying thrips flap their densely bristled wings at large stroke amplitudes, bringing both wings in close proximity of each other at the end of upstroke ('clap') and moving their wings apart at the start of downstroke ('f… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…In addition, pausing before the start of fling has been shown to reduce power required. 17 Moreover, when the ratio of membrane area to the total area of the wings is in the range of Thrips' wings, the bristled wings have the largest lift to drag ratio in the "fling" motion 18 . Recently, a study by Lee et al 19 found that the bristled wings could alleviate the undesired aerodynamic loading induced by gusty flow.…”
Section: Openmentioning
confidence: 99%
“…In addition, pausing before the start of fling has been shown to reduce power required. 17 Moreover, when the ratio of membrane area to the total area of the wings is in the range of Thrips' wings, the bristled wings have the largest lift to drag ratio in the "fling" motion 18 . Recently, a study by Lee et al 19 found that the bristled wings could alleviate the undesired aerodynamic loading induced by gusty flow.…”
Section: Openmentioning
confidence: 99%